Empirical Analysis on the Elements of a Good Tax System and Tax Compliance in Nigeria - Sopekan, Adeyemi Samuel; Olaniyi, Taiwo Azzezz; Aronmwan, Edosa Joshua; Adegboyega, Ayodeji Hakeem (Universitas Negeri Semarang, 2025)
Purpose : The study evaluates the relationship between the elements perceptions of a good tax system – simplicity and fairness – and tax compliance. Method : The survey was conducted using Cochran’s sampling technique with 384 respondents, drawn from personal and corporate income taxpayers, tax professionals, and tax officials across Nigeria. This study uses Partial Least Square Structural Equation Modelling (PLS-SEM) to analyse the relationship of tax simplicity and tax fairness with tax compliance. Findings : The study found that there is a significant relationship between tax simplicity and tax compliance. It was also found that tax fairness perception has a substantial relationship with tax compliance. Novelty : Some earlier studies have identified varied factors affecting tax compliance behaviour such as audits, tax education, trust in tax authorities and tax morale. This study identifies the interplay of tax simplicity and fairness in determining the tax compliance behaviour. It underscores that in a well-structured tax system, characterised by streamlined tax laws, if tax can be levied on taxable objects (people or organisations), then tax can provide benefits to both taxable objects and the government.